Pengaruh Pemasaran Cross selling, Pemasaran Viral, dan Pemasaran Produk Bundling Terhadap Keputusan Pembelian Pada Produk Skintific (Studi Pada Konsumen di Kecamatan Lowokwaru Kota Malang) - Lukyani, Defita; Arifin, Rois; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the impact of cross-selling marketing, viral marketing, and product bundling marketing on the purchasing decisions of Skintific products in Malang City. Employing a multiple linear regression method, this study focuses on Explanatory research employing quantitative methods. The sample of 90 consumers was determined using the Malhotra formula. Data analysis was conducted using SPSS version 25, including validity testing, reliability testing, normality testing, classic assumption testing, hypothesis testing, and the determination coefficient test (R2). The results show that overall, cross-selling marketing, viral marketing, and product bundling marketing significantly influence the purchasing decisions of Skintific product consumers in Lowokwaru District, Malang. Specifically, cross-selling marketing and viral marketing have a positive impact on purchasing decisions, while product bundling marketing does not have a significant influence on consumer purchasing decisions. Keywords: Cross-Selling Marketing, Viral Marketing, Product Bundling Marketing, Purchase Decision